Leadership System of Adat Perpatih In Malaysia As A Model of Consensus and Democracy Concept: An Analytical Study - Mualimin Mochammad Sahid; Mohammad Chaedar; Baidar Mohammed Mohammed Hasan; Fettane Amar (Psychology And Education, 2024)
Indexed by ERA